Autonomous Taxation in Portugal: The Cost of a Tricky Law (International Journal of Business Innovation, 2024)
Tax complexity is a reality of modern tax systems in both developed and developing countries, as tax regimes have a significant impact on current and future business decisions. In Portugal, an additional tax, known as autonomous taxation, applicable to all taxpayers of corporate income tax, henceforth CIT, levied on certain charges that are not related to the activity of companies, which may be considered inconvenient or associated with evasive or even fraudulent practices. The objective of this research is to examine the subject of autonomous taxation in the context of tax arbitration case law in Portugal. Consequently, the arbitration decisions in which the complexity of autonomous taxation is referenced are analysed. The intention is to ascertain the reasons for this complexity and the resulting costs. The investigation carried out allows us to conclude that the complexity of Portuguese  tax system, more specifically, the complexity of autonomous taxation, may be related to the frequent changes in legislation, the uncertainty arising from the law and the diversification of tax rates, as well as the tax burden borne by taxpayers, which will lead to an increase in the number of disputes in the arbitration courts and, consequently, the cost of the proceedings, will remain high.
Keywords: Autonomous Taxation; Fiscal Complexity; Litigation; Costs